Utilization of Eco-Enzyme on Land Spinach (Ipomoea reptans Poir.) with Wick Hydroponic System - Listiana, Ika; Ayuni, Tri; Saputri, Dwijowati Asih; Amelia, Iqlima (Biospecies, 2024)
Eco-enzyme is a liquid produced by utilizing leftover fruits or vegetables with the addition of molasses and water, which are then fermented. This study utilized materials such as orange peel, pineapple peel, and watermelon peel. The objective of this research was to determine the content and the effect of applying eco-enzyme on land spinach plants (Ipomoea reptans Poir.) using a wick hydroponic system. This quantitative experimental research was conducted from January to July 2023 at the Analytical Laboratory of Lampung State Polytechnic and the Integrated Laboratory & Technology Innovation Center of the University of Lampung. The observed parameters included plant height, number of leaves, and leaf length. The study employed a Completely Randomized Design (CRD) with four treatments, one of which served as the control, and each experimental unit was replicated five times. A total of 160 plant samples were used, and measurements were taken every 7 days for a period of 30 days. The data were analyzed for variance and subjected to Tukey's test at a significance level of a = 5%. The research findings revealed that:1) The utilization of eco-enzymes with different treatments has an impact on all observed parameters in the growth of land spinach (Ipomoea reptans Poir.), 2) The best treatment was found in the P4 treatment with an eco-enzyme dose of 6 ml/L.